Maximum Stress Analysis on Ship Anchor Chains with Various Force Angles - Chris Jeremy Verian Sitorus; Luluh Wardah; Alamsyah; Suardi; Andi Mursid Nugraha Arifuddin; Samsu Dlukha Nurcholik; Hariyono; Jusma Wahidah; Harlian Kustiwansa; Ahmad Azwar Mas`ud M (National Research and Innovation Agency (BRIN Publishing), 2025)
One of the components of ship fittings is the anchor chain. Usually, when the anchor is moored, it is not always positioned perpendicular to the ship’s hull; instead, it often forms an angle between the chain and the hull. Due to environmental influences or excessive tension occurring at certain angles, there have been cases of anchor chains breaking. Therefore, it is necessary to conduct a maximum stress analysis of the ship’s anchor chain with varying force angles to determine the maximum stress experienced by the chain. This research focuses on the anchor chain of the Tug Boat Marina 2435 and utilizes ANSYS Workbench for finite element analysis. In this research, the chain is suspended from the hawse pipe with a diameter of 19 mm, and the loading on the anchor chain is static, consisting of the weight of the chain and the anchor. The angles analyzed are 30°, 35°, 40°, 45°, 50°, 55°, and 60°. The maximum stress on the anchor chain was observed at an angle of 35°, with a value of 6.9943 MPa. The stress at each angle remained below the ultimate tensile strength of the material, which is 515 MPa.